Electrocatalytic reduction of carbon dioxide: opportunities with heterogeneous molecular catalysts. Issue 2 (17th January 2020) - Sun, Libo; Reddu, Vikas; Fisher, Adrian C.; Wang, Xin
Abstract : Electrocatalytic CO2 reduction by heterogeneous molecular catalysts is emerging as an important area for CO2 utilization. Abstract : Electrocatalytic CO2 reduction by heterogeneous molecular catalysts is emerging as an important area for CO2 utilization. Unlike commonly used solid heterogeneous catalysts, molecular catalysts possess well-defined structure, which allows the establishment of a precise structural model for better understanding of the CO2 reduction mechanism. The easy modification of molecular catalysts with designated functional fragments through organic synthesis skills also facilitates the development of novel and efficient molecular catalysts. The direct use of molecular catalysts in the homogeneous phase suffers from poor solubility in some common solvents, low utilization and difficulty in recycling. Heterogeneous immobilization of molecular catalysts onto a substrate can potentially solve these problems. This review summarizes the methods that have been developed so far for heterogeneous immobilization of homogeneous molecular catalysts, including covalent/non-covalent bonding, and assembling the molecular catalysts into a periodic skeleton. Challenges and factors affecting the activities of such catalysts in electrochemical CO2 reduction are also discussed.